2022
DOI: 10.3390/joitmc8040198
|View full text |Cite
|
Sign up to set email alerts
|

Lurkers versus Contributors: An Empirical Investigation of Knowledge Contribution Behavior in Open Innovation Communities

Abstract: This study aims to examine and compare the mechanisms through which social learning processes influence the knowledge contribution behavior of lurkers and contributors in open innovation communities (OICs). Based on social learning theory and stimulus–organism–response (SOR) framework, this study developed a model of knowledge contribution formation mechanism from environmental stimuli (observational learning, reinforcement learning), organism cognition (self-efficacy, outcome expectancy) to behavioral respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Therefore, it is convenient to find a sufficient sample of contributors to study and compare the interaction dynamics between the motivating factors of value co-destruction in the OIC. In addition, the large user base provided a valuable source of data for previous academic studies [ 4 , 5 , 58 ]. Therefore, as successful professional OICs, these innovation communities can serve as a typical case study for academic research and provide useful suggestions for the development of other OICs [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is convenient to find a sufficient sample of contributors to study and compare the interaction dynamics between the motivating factors of value co-destruction in the OIC. In addition, the large user base provided a valuable source of data for previous academic studies [ 4 , 5 , 58 ]. Therefore, as successful professional OICs, these innovation communities can serve as a typical case study for academic research and provide useful suggestions for the development of other OICs [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the large user base provided a valuable source of data for previous academic studies [ 4 , 5 , 58 ]. Therefore, as successful professional OICs, these innovation communities can serve as a typical case study for academic research and provide useful suggestions for the development of other OICs [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, lurkers' and posters' behavior within the community seems different-but these groups are similar in many other ways. For example, Daradkeh (2022) found that lurkers and posters were likelier to post when they expected positive outcomes due to their participation and felt they had the necessary knowledge to contribute effectively. Perhaps posters are more likely to think they possess the skills needed to gain positive reinforcement for their behavior.…”
Section: Lurkers Versus Postersmentioning
confidence: 99%